Non-myeloablative conditioning is sufficient to achieve complete donor myeloid chimerism following matched sibling donor bone marrow transplant for myeloproliferative leukemia virus oncogene (MPL) mutation-driven congenital amegakaryocytic thrombocytopenia: Case report - Oved, Joseph Hai; Shah, Yash B.; Venella, Kimberly; Paessler, Michele E.; Olson, Timothy S. (Frontiers in Pediatrics, 2022)
Background: Congenital amegakaryocytic thrombocytopenia (CAMT) is a rare disorder of platelet production that is most commonly caused by loss of function biallelic mutations in MPL, the gene encoding the thrombopoietin receptor (TPOR). Patients with MPL-mutant CAMT are not only at risk for life-threatening bleeding events, many affected individuals will ultimately develop bone marrow aplasia owing to absence of thrombopoietin/TPOR signaling required for maintenance of hematopoietic stem cells. Curative allogeneic stem cell transplant for patients with CAMT has historically used myeloablative conditioning; however, given the inherent stem cell defect in MPL-mutant CAMT, a less intensive regimen may prove equally effective with reduced morbidity, particularly in patients with evolving aplasia. Methods: We report the case of a 2-year-old boy with MPL-mutant CAMT and bone marrow hypocellularity who underwent matched sibling donor bone marrow transplant using a non-myeloablative regimen consisting of fludarabine, cyclophosphamide and ATG. Results: The patient achieved rapid trilinear engraftment and resolution of thrombocytopenia. While initial myeloid donor chimerism was mixed (88% donor), due to competitive advantage of donor hematopoietic cells, myeloid chimerism increased to 100% by 4 months post-transplant. Donor chimerism and blood counts remained stable through 1-year post-transplant. Conclusions: This experience suggests that non-myeloablative conditioning is a suitable approach for patients with MPL-mutant CAMT undergoing MSD-BMT and is associated with reduced risks of conditioning related toxicity compared to traditional myeloablative regimens.